1983
DOI: 10.1364/ao.22.000178
|View full text |Cite
|
Sign up to set email alerts
|

Ion-beam-assisted deposition of thin films

Abstract: Some effects on the properties of electron-beam evaporated thin films produced by ion bombardment of the growing film are reported. Substantial increases in the packing densities of SiO2 , TiO2 , and ZrO2 films have been produced as measured by the reduction in the adsorption of moisture when the films are exposed to a humid atmosphere. In a ZrO2-SiO2 multilayer interference filter, changes in the wavelength of the peak transmittance on exposure to the atmosphere have been reduced from 8 nm for films deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(54 citation statements)
references
References 0 publications
3
50
1
Order By: Relevance
“…It is known that the response time of dielectric films are dependent on their morphology and porosity [3,4]. The ZrO 2 WG was evaporated by EB-PVD and is more porous than the Dralo WG, which was evaporated by IBAD [25]. According to [4] and [7], the increase in porosity amounts to decreasing the response time, which is in agreement with our findings.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It is known that the response time of dielectric films are dependent on their morphology and porosity [3,4]. The ZrO 2 WG was evaporated by EB-PVD and is more porous than the Dralo WG, which was evaporated by IBAD [25]. According to [4] and [7], the increase in porosity amounts to decreasing the response time, which is in agreement with our findings.…”
Section: Resultssupporting
confidence: 91%
“…Therefore, IBAD films are more compact, and this reduced porosity makes them less sensitive to moisture. These facts were corroborated by structural and textural characterization, including SEM micrographs [25]. However, this difference can be circumvented by changing the position of the CCD, as described earlier, such that the response of the WG sensor does not depend significantly on the dielectric material.…”
Section: Methodsmentioning
confidence: 58%
See 1 more Smart Citation
“…Each of the fo ur organisms was found to have its own unique group of compounds that could serve either individually or in combination as sources of carbon and energy for growth . When the peptone in the medium was replaced by another appropriate source of carbon and energy, the difference in the capacities of the organisms examined to grow at low nutrient concentration disappeared, and all four organisms could be described as oligotrophic (32). We concluded that the methods being used to distinguish oligotrophic and eutrophic bacteria were not in fact doing so.…”
Section: Other Studiesmentioning
confidence: 92%
“…SuperPower is using nontextured metal substrates and obtain a bi-axial textured buffer layer by Ion Beam Assisted Deposition (IBAD) (34) followed by Metal Organic Chemical Vapor Deposition (MOCVD) of the YBCO layer (2).…”
Section: Hts Conductorsmentioning
confidence: 99%